Charlie a'r Ffatri Siocled - Dahl, Roald,Meek, Elin,Blake, Quentin (Rily Publications Limited, 2010)
A Welsh adaption of the famous story of Charlie and the Chocolate Factory by Roald Dahl.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books